THE INFLUENCE OF SMARTPHONES ON CHILD DEVELOPMENT: A PSYCHOLOGICAL AND EDUCATIONAL ANALYSIS - Juli Andriani Juli Andriani (STAI Nusantara Kota Banda Aceh, 2024)
The introduction of smartphones to children can have a significant impact and influence on children both physically and mentally. The impacts and influences can be both positive and negative influences on a child's development. Therefore, the supervision factor of parents and teachers is very necessary in protecting children from the influence of smartphones. smartphones can affect aspects of cognitive development, social-emotional, religious and moral values, language and physical-motor aspects of children. Appropriate and correct use of smartphones can be a stimulating medium that is able to develop all aspects of child development optimally in accordance with their age stages. On the other hand, excessive and unsupervised use of smartphones will also have a negative impact on children's development in the future. Many things affect children based on the review of educational psychology. Educational psychology is a branch of psychology that focuses on understanding how humans learn and teach in the context of education. It is a discipline that studies the cognitive, emotional, social and behavioural processes of individuals involved in learning and teaching. So, parents and teachers today must supervise their children's activities, especially in using smartphones, which are feared to have a negative impact on children's development later.